Determining the effect of plasmochemically activated aqueous solutions on the bioactivation process of sea buckthorn seeds - Kovalova, Olena; Vasylieva, Natalia; Stankevych, Serhii; Zabrodina, Inna; Haliasnyi, Ivan; Gontar, Tatiana; Kotliar, Oleh; Gavrish, Tatiana; Gill, Michael; Karatieieva, Olena (Eastern-European Journal of Enterprise Technologies, 2023)
The studies revealed the regularities of obtaining bioactivated sea buckthorn seeds using plasma-chemically activated aqueous solutions during germination. Sea buckthorn seeds were chosen as the research object. Plasma-chemically activated aqueous solutions were used to activate the germination process. This made it possible to solve the problem of processing waste from the production of sea buckthorn oil, and also contributed to obtaining a high-quality component of food products. Experimental studies have proven the effectiveness of using plasma-chemically activated aqueous solutions as effective intensifiers and disinfectants for the process of bioactivation of sea buckthorn seeds. It is shown that their use intensifies the germination of sea buckthorn seeds, contributes to a more active accumulation of biologically valuable components in the seeds. Plasma-chemically activated aqueous solutions with a peroxide concentration of 300–700 mg/l were used. An increase in the geometric parameters of seeds, namely length by 8.5–14.9 % and width by 3.7–14.8 %, was recorded. The germination energy increased by 5–13 % and germination capacity by 5–14 %. The composition of sea buckthorn seeds, both derived raw material and bioactivated, was investigated. Studies have shown that bioactivated seeds contain an increased amount of highly valuable substances. The protein content increased by 4 % compared to sea buckthorn seeds and by 1.7 % compared to the control. The lipid content increased by 2 and 1.1 %. An increase in the content of vitamins was noted: B1, B2, C, A, E, R. The amount of amino acids increased by 9–13 % compared to the control, and compared to the original raw material – by 1.5–3.5 times. In addition, plasma-chemically activated aqueous solutions effectively disinfected the raw material. The presented technology can be used in the food processing industry